Do pharmaceuticals bioaccumulate in marine molluscs and fish from a coastal lagoon? - Moreno-González, R.; Rodríguez-Mozaz, S.; Huerta, B.; Barceló, D.; León, V. M. (Environmental Research, 2016)
The bioaccumulation of 20 pharmaceuticals in cockle (Cerastodema glaucum), noble pen shell (Pinna nobilis), sea snail (Murex trunculus), golden grey mullet (Liza aurata) and black goby (Gobius niger) was evaluated, considering their distribution throughout the Mar Menor lagoon and their variations in spring and autumn 2010. The analytical procedure was adapted for the different matrices as being sensitive and reproducible. Eighteen out of the 20 compounds analysed were found at low ngg−1 in these species throughout the lagoon. Hydrochlorothiazide and carbamazepine were detected in all species considered. The bioaccumulation of pharmaceuticals was heterogeneous in the lagoon, with a higher number of pharmaceuticals being detected in fish (18) than in wild molluscs (8), particularly in golden grey mullet muscle (16). В-blockers and psychiatric drugs were preferentially bioccumulated in fish and hydrochlorothiazide was also confirmed in caged clams. The higher detection frequency and concentrations found in golden grey mullet suggested that mugilids could be used as an indicator of contamination by pharmaceuticals in coastal areas. To the best of our knowledge, this is the first study that shows data about hydrochlorothiazide, levamisole and codeine in wild marine biota.
Keywords: Bioaccumulation; Bivalve; Coastal lagoon; Distribution; Fish; Gastropod; Pharmaceuticals; Seasonality; dept.che